PERGESERAN PEMAKNAAN TERHADAP TRADISI JE’NE LIMBUA - Pratiwi Nur (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2023)
A culture that has been passed down from generation to generation in the province of South Sulawesi, to be precise in Jeneponto Regency, Beroanging Village, namely the Je'ne Limbua Tradition. Where some people still carry out this tradition, there are several procedures for carrying out the Je'ne Limbua Tradition. This tradition aims to carry out their intentions or vows. By maintaining this tradition, the local community believes that the economic and social factors in the area will be stable. According to the theory of the Sacred and the Profan which was initiated by Mircea Eliade, the writer used it to find out the shift in meaning that occurred in the Je'ne Limbua Tradition in Beroanging Village, West Bangkala District, Jeneponto Regency, South Sulawesi. And there are 3 groups of people who respond to the Je'ne Limbua Tradition, namely, 1) people who believe, 2) people who doubt, and 3) people who don't believe.